Recent advances of photoresponsive nanomaterials for diagnosis and treatment of acute kidney injury - Shijie Yao; Yinan Wang; Xiaozhou Mou; Xianghong Yang; Yu Cai (Journal of Nanobiotechnology)
Abstract Non-invasive imaging in the near-infrared region (NIR) offers enhanced tissue penetration, reduced spontaneous fluorescence of biological tissues, and improved signal-to-noise ratio (SNR), rendering it more suitable for in vivo deep tissue imaging. In recent years, a plethora of NIR photoresponsive materials have been employed for disease diagnosis, particularly acute kidney injury (AKI). These encompass inorganic nonmetallic materials such as carbon (C), silicon (Si), phosphorus (P), and upconversion nanoparticles (UCNPs); precious metal nanoparticles like gold and silver; as well as small molecule and organic semiconductor polymer nanoparticles with near infrared responsiveness. These materials enable effective therapy triggered by NIR light and serve as valuable tools for monitoring AKI in living systems. The review provides a concise overview of the current state and pathological characteristics of AKI, followed by an exploration of the application of nanomaterials and photoresponsive nanomaterials in AKI. Finally, it presents the design challenges and prospects associated with NIR photoresponsive materials in AKI. Graphical Abstract